A macroscopic traffic model based on relaxation time - Zawar Hussain Khan (Alexandria Engineering Journal, 2022)
A macroscopic model based on analogies with Little’s Law is proposed. The relaxation time is employed to characterize changes in density. This change is large for a small relaxation time and large interactions between vehicles occur. The relaxation time encompasses driver behavior which includes the time to perceive and process traffic situations and the resulting actions. Thus, it incorporates the perception and reaction time of a driver. The proposed model is evaluated for a transition caused by a bottleneck on a road and is compared with Zhang model. Performance results are presented which show that traffic evolution with the proposed model is more realistic than with the Zhang model.